Analysis of Inconsistent Routing Components in Reactive Routing Protocols - Rehman, Habib-ur; Wolf, Lars (Electronic Communications of the EASST, 2009)
In reactive routing protocols, additional routing information is often collected to reduce the response time and the overhead of the future routing demands. However, these protocols do not have any mechanism to refresh this routing information and soon it become obsolete. Therefore, routing components based on this prior-to-demand collected information are not consistent with the reactive nature of the protocol. In this work, we have identified such inconsistent components in AODV routing protocol and have analyzed their effect. Our simulation based analysis has revealed that the presence and use of stale routing information degrades the protocol performance. However, if the dependency of protocol operations on this obsolete information is reduced, the protocol performs better in terms of overhead and packet delivery ratio.